Musescore Software Training for the Development of TPACK-Based Music Learning in Elementary Schools: Pelatihan Software Musescore untuk Pengembangan Pembelajaran Musik Berbasis TPACK di Sekolah Dasar - Karsono; Joko Daryanto; Rukayah; Tri Budiharto; Ayyas Yahya; Mukhlis Anton Nugroho (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Digital literacy and the skills of elementary school teachers in choosing and using scoring applications (musical notation) as a medium as well as a learning resource for students are essential to do. Elementary school education is experiencing several problems today, such as the government's inability to provide training on using applications for the learning process. In addition, not all teachers have the confidence in choosing and determining computer application software that can support learning in class, especially in the subject matter of Cultural Arts and Crafts (SBdP) material in the field of music. Elementary school teachers in the Laweyan sub-district of Surakarta do not yet have optimal insight regarding developing music applications to support material delivery in class. This community service activity is focused on training elementary school teachers to use music scoring (notation) software with the Musescore application. The results of this training found the formation of teacher skills using the Musescore music application to support music learning in elementary schools.